Securing cloud services : a pragmatic guide - Newcombe, Lee (IT Governance Publishing, 2020)
Securing Cloud Services - A pragmatic guide gives an overview of security architecture processes and explains how they may be used to derive an appropriate set of security controls to manage the risks associated with working in the Cloud. Manage the risks associated with Cloud computing - buy this book today!